CentaureaL. sectionPhrygiaPers.: phylogeny and biogeography - FILIGHEDDU, Rossella Speranza (Università degli studi di Sassari, 2012)
Molecular systematics, along with other biosystematic approaches, is an essential tool when trying to decipher the natural relationships among taxa, and in complex groups, such asCentaureaL., this approach seems useful, if not necessary.Centaureais one of the largest genera of the Compositae and its taxonomic treatment has always been complicated. In particular, the sectional delineation of sectionsJacea(Mill.) DC. andPhrygiaPers. (=Lepteranthusnom. inval.) has been controversial for long time. The present review tries to elucidate nomenclature and systematics of sect.Phrygia. Furthermore, taxonomy of morphologically related Iberian species belonging to sect.Phrygiahas historically presented many problems. In order to clarify it, an integrative study with morphological and molecular data was used. Moreover, a genetic study of two closely related narrow endemic species was conducted to decipher the evolutionary processes occurring in sect.Phrygiaat low scale and to propose the most appropriate conservation strategies. Finally, the study ofCentaureasect.Phrygiahas led to the discovery of a new species which was unnoticed in the herbaria for years,Centaurea tripontinaLópez-Alvarado, L. Sáez, Filigheddu, Guardiola and Susanna.